Comment on "On the calculation of lake metabolic rates: Diel O2 and 18/16O technique" by Peeters et al. [Water Res. 165 2019, 114990]. (1st August 2020) - Bogard, Matthew J.; Butman, David E.; del Giorgio, Paul A.
Abstract: Quantifying metabolic rates in lakes and other aquatic ecosystems is a complex task, as methods are continually evolving and are not currently standardized. Recently, Peeters et al. presented a valuable simulated dataset that advances the field by comparing the strengths and limitations of individual and combined metabolic techniques. The authors conclude that calculating metabolic rates from point sampling and mass balancing of surface water oxygen concentration and isotope composition is flawed, because the technique does not capture sub-daily patterns of metabolic variability, which they argue invalidates past applications and interpretations. These conclusions are inconsistent with how the method has been used, and are based on a biased construction of scenarios and interpretation of model results, especially because their parameterization of the stable isotopic model employs input values that appear unrepresentative of most lake conditions. Here, we establish that 1) empirical evidence supports the isotopic approach's suitability to approximate daily or longer metabolic patterns in most lakes. 2) The authors' own simulations show agreement between metabolic estimates from point isotopic measurements and average metabolic rates under most scenarios. 3) The authors' invalidation of isotopic measurements are based on the most extreme model deviations observed in simulated hypereutrophic environments. While we welcome a critical evaluation of the isotopic approach, we argue that isotopic model uncertainty needs to be placed within an appropriate context. We emphasize that isotopic sampling and steady state metabolic modelling has a key role to play in constraining metabolic patterns in the global lake landscape, but that the research questions addressed with the method need to be commensurate with the limitations and uncertainties of the approach. Highlights: Point isotopic measurements provide reliable daily metabolic averages. Peeters et al.'s simulations show mid-day point metabolic sampling is accurate. Past results/findings from isotopic method supported by independent datasets.